Con ell arco de la ffe: a spiritual reading of the badge of the arrows of Isabella the Catholic - Narbona Cárceles, María (Eikón / Imago, 2025)
This article offers a hypothesis about the interpretation of the badge of the arrows of Isabella I of Castile, based on a spiritual reading of the emblem. The starting point is the messianic conception that the Catholic Monarchs had of their mission as rulers from very early on, as well as the idea of crusade against the infidel. The study is based on various sources that would have inspired the creation of the badge: chapter 49 of the book of Isaiah and Psalm 45 and the commentaries made on the subject by some Fathers of the Church and some medieval authors, as well as the Legend of Saint Ursula and the eleven thousand virgins, based on the Legenda aurea by Jacobus de la Voragine and its Spanish version, the Flos sanctorum. The study also takes into account the complexity of the circumstances in which the badge of the Elizabethan bundle of arrows was made, between 1469 and 1473.